Analysis of Production and Income of Tomato Farms Village-owned and Non Village-owned Tomato Farms Kulisusu District, North Buton Regency - Lilis, Lilis; Marsuki Iswandi; Lukman Yunus (International Journal of Technology and Education Research, 2024)
This study aims to determine: (1) Production of BUMDes tomato farming and non-BUMDes tomato farming of Kulisusu District, North Buton Regency, (2) Income of BUMDes tomato farming and non-BUMDes of tomato farming of Kulisusu District, North Buton Regency and (3) Differences in BUMDes tomato farming income and non-BUMDes tomato farming in Kulisusu District, North Buton Regency. The location was determined purposively, this research was conducted in October 2022 - June 2023. The number of respondents was 35 people consisting of 20 BUMDes tomato farming respondents and 15 non-BUMDes tomato farming respondents. The analysis used to answer the first problem statement used descriptive analysis, to answer the second problem statement used income analysis and to answer the third problem statement used an analysis of the average difference test (compare means) independent sample t-test method. The results showed that the average BUMDes tomato farming yield was 2,830/Kg/ha and the Non-BUMDes tomato farming production yielded an average of 2,233/kg/ha. The average BUMDes tomato farming income is IDR 28,018,349/Ha while the non-BUMDes tomato farming average is IDR 24,477,344/Ha. The results of the average different test show that the difference in BUMDes tomato farming income and non-BUMDes tomato farming has a significant effect on income showing a sig value. (2-tailed) 0.03<0.05.